Transforming gum wastes into high tap density micron-sized carbon with ultra-stable high-rate Li storage. (20th January 2021) - Cheong, Jun Young; Venkateshaiah, Abhilash; Yun, Tae Gwang; Shin, Sung-Ho; Černík, Miroslav; Padil, Vinod V.T.; Kim, Il-Doo; Varma, Rajender S.
Highlights: Synthesis of MFC from low-grade gum wastes. The synthesized MFC possesses high tap density (1.4–1.7 g cm −3 ). High tap density leads to outstanding volumetric capacity at 3.0 A g −1 . MFC also exhibits ultra-stable high-rate cyclability (0.001881% decrease per cycle). Structural integrity was well maintained even after cycling. Abstract: Among various natural wastes, gum wastes pose major issues, as they are unusable and hard to be disposed due to their acidic and sticky nature. Herein, a rational synthetic strategy is employed to transform various kinds of gum wastes into micron-sized carbon, which also exhibit high tap density (1.4–1.7 g cm −3 ) desirable for practical application in lithium-ion batteries (LIBs). Gum karaya (GK) micron-size functional carbon (GKMFC) exhibits the most outstanding electrochemical performance, with a volumetric capacity of 175.4 mAh cm −3 at a current density of 3000 mA g −1 for 5000 cycles, and possesses ultra-stable high-rate cyclability (a capacity decay of only 0.001881% per cycle). Additional electrochemical analyses reveal that GKMFC exhibits stable structural integrity as well as minimal cell resistance even after cycling, showing its practical application as viable electrode for LIBs. This work sheds light on utilizing high tap density carbon from gum wastes for LIBs, which can also be applicable to other natural wastes and carbon. Graphical abstract: Image, graphical abstract